Hubungan Minat Belajar dan Lingkungan Belajar dengan Prestasi Siswa pada Mata Pelajaran Instalasi Penerangan Listrik - Sukarman Purba; Sadat Zulgani; Joan Emanuella Sitorus; Kevin Stefhani Telaumbanua; Putri Kaylana Pasyah (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to determine the relationship between learning interest and learning environment with student achievement in the Electrical Lighting Installation subject at SMKS Sinar Husni 2 TR Labuhan Deli. The study used a quantitative approach with a correlational design. The study population was 45 students of class X Electrical Power Installation Engineering (TITL), while the research sample was 20 students selected using a random sampling technique. Data on learning interest and learning environment were collected through a questionnaire, while student achievement data were obtained from the documentation of Electrical Lighting Installation subject scores. Data analysis was carried out using Pearson Product Moment correlation to test partial relationships and multiple correlations to test simultaneous relationships between variables with the help of SPSS version 27. The results showed that learning interest had a positive relationship with student achievement with a correlation coefficient of 0.680 which is included in the strong category. The learning environment also had a positive relationship with student achievement with a correlation coefficient of 0.718 which is included in the strong category. Simultaneously, learning interest and learning environment had a positive relationship with student achievement. These findings indicate that the increase in student achievement in the Electrical Lighting Installation subject is influenced by internal factors in the form of learning interest and external factors in the form of the learning environment. Therefore, increasing interest in learning and creating a conducive learning environment are essential for improving student achievement.